(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
This paper formally describes some cranial and postcranial remains of young and adult fossil suids retrieved from Monte Tuttavista karst fissures (Orosei, western Sardinia). The material is herein attributed to the Sardinian species Sus sondaari Van der Made, 1999. Features of skulls, mandibles, some milk teeth, definitive canines, and thus far unknown post-cranial elements of Monte Tuttavista suids significantly integrate our knowledge of the endemic species Sus sondaari. An emended diagnosis is here proposed, including some new diagnostic features such as lower canine with scrofic section, and oval shape of scapular glenoid fossa. Finally, the challenging evolutionary relationships of Sus sondaari are briefly discussed.